q+7-2(q-2)=3(2q+1)+5q

Simple and best practice solution for q+7-2(q-2)=3(2q+1)+5q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for q+7-2(q-2)=3(2q+1)+5q equation:


Simplifying
q + 7 + -2(q + -2) = 3(2q + 1) + 5q

Reorder the terms:
q + 7 + -2(-2 + q) = 3(2q + 1) + 5q
q + 7 + (-2 * -2 + q * -2) = 3(2q + 1) + 5q
q + 7 + (4 + -2q) = 3(2q + 1) + 5q

Reorder the terms:
7 + 4 + q + -2q = 3(2q + 1) + 5q

Combine like terms: 7 + 4 = 11
11 + q + -2q = 3(2q + 1) + 5q

Combine like terms: q + -2q = -1q
11 + -1q = 3(2q + 1) + 5q

Reorder the terms:
11 + -1q = 3(1 + 2q) + 5q
11 + -1q = (1 * 3 + 2q * 3) + 5q
11 + -1q = (3 + 6q) + 5q

Combine like terms: 6q + 5q = 11q
11 + -1q = 3 + 11q

Solving
11 + -1q = 3 + 11q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-11q' to each side of the equation.
11 + -1q + -11q = 3 + 11q + -11q

Combine like terms: -1q + -11q = -12q
11 + -12q = 3 + 11q + -11q

Combine like terms: 11q + -11q = 0
11 + -12q = 3 + 0
11 + -12q = 3

Add '-11' to each side of the equation.
11 + -11 + -12q = 3 + -11

Combine like terms: 11 + -11 = 0
0 + -12q = 3 + -11
-12q = 3 + -11

Combine like terms: 3 + -11 = -8
-12q = -8

Divide each side by '-12'.
q = 0.6666666667

Simplifying
q = 0.6666666667

See similar equations:

| 1/2x+5+1/3x-5 | | 2a-10=2 | | 13n=42-3 | | 7x+6=9x | | 3x/x-5-5/x-2 | | 13x+195=13(3x+15) | | 4/3z-7+2/3z=-1 | | 88-5x=2x+11 | | -6/x-5-8/x+7 | | 15X+3-7X+4-8X=0 | | 144x^3-258x^2+105x=0 | | pi=3.1416 | | 2x+6/4+5x-2/8 | | 1/2t=-13 | | 7(x-1)=2(2x+4) | | 4x+z=19 | | X+3.5=8.8 | | -x^2-6x+5y^2+10y=22 | | 7(x-5)+14=-7 | | 6x+3=8x-3x | | 12t^2+32t=12 | | 1/2y=1.5 | | 2n/5=30 | | 3z+5z-2=0 | | 261=195-u | | 3x^5-39x^3+108x=0 | | 4x-3/1-6x=x-7/x+9 | | 7x+5=2x+85 | | 3x^3+10x^2-27x=10 | | 5x+51=7x-7 | | 12y^2-41y=-35 | | 2n*5=30 |

Equations solver categories